Kajian Potensi Angin Laut Sebagai Sumber Energi Terbarukan Pembangkit Listrik Pulau Kecil di Pesisir Utara Provinsi Papua - Johni Jonatan Numberi; Samuel P. Siregar; Tiper K. M. Uniplaita; Rombe Allo; Anastasya S. Werdhani; Joni Joni; Pither Palamba; Marthen Liga; Theresia W. Oktaviani; Matius R. Manalu (Fakultas Teknik Universitas Pancasila, 2023)
Papua province has nine small islands that are inhabited, but there is no access to electricity on these islands. The solution is the use of sea wind as a source of energy for a small power plant. This study aims to determine the potential of sea wind as an alternative source of electrical energy on the north coast of Papua Province. Data Measurement is carried out using an HP-866B anomometer on a hill near the coast to maximize the sea wind. There are two methods used in this research: the minimum-maximum value to determine the wind speed range and linear regression to determine the distribution pattern of the wind. The range of the sea wind is 0.2–6.18 m/s. If the minimum speed is limited to 1.6 m/s, then the range of kinetic energy is 5.59–322.22 Joules/s, mechanical power is 5.59–322.22 Watts, and actual power is 0.57–33.13 Watts. Meanwhile, the pattern shows that the sea wind from the north coast of Papua Province blows with two trends: constant and increasing, specifically in the afternoon and evening. Based on that, the development of a wind power plant on the north coast of Papua Province can be carried out using a multi-turbine system to increase the actual power that can be obtained.